Relationship Between Vitamin D Supplementation and Improvement in Body for Carcinogenesis: A Literature Review - Irawan Sastradinata; Rizal Sanif; Cindy Kesty; Siti Hardianti Harahap (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Vitamins are probably the best-selling dietary supplements in the United States, in which an estimated 35% of the population take multivitamin and mineral supplements. Data relating microconstituents to carcinogenesis are extremely limited, as explained in the first report. A striking feature of many of the compounds in the three groups mentioned above is their capacity to prevent or retard the occurrence of neoplasia. However, there is a paucity of data concerning the conditions under which inhibition occurs, the mechanisms of inhibition, and the precise impact of these microconstituents on humans. A literature review was conducted in the electronic databases PubMed and Google Scholar using the index terms "carcinogenesis" and "cancer" and "vitamin D" All types of studies were included for this study, such as randomized controlled trials, systematic reviews, literature reviews, and pilot studies published between 2010 and 2021. Articles which not written in English were excluded from the study. This search resulted in 10 papers. Many of the mechanisms proposed for vitamin D and cancer prevention have been studied only in the context of one tissue or one type of cancer and so further studies must be conducted to determine if these mechanisms can be generalized. For example, while higher serum (25(OH)D3) is associated with reduced cancer risk, and CYP27B1 is expressed in non-renal cells, there is no evidence that the low-level expression of CYP27B1 in tissues leads to meaningful local production of 1a,25(OH)2D3 or calcitriol, and that this mediates the protection from cancer provided by high vitamin D status. In conclusion, we suggest that vitamin D compounds to be employed in the treatment of, alone or in combination with other anticancer agents. solar UV-B radiation, acting through the production of vitamin D, is a risk reduction factor for over a dozen forms of cancer.